Differential phase angle spectrum for liquid detection in functionalized surface roughness polymeric electrode - Gomez-Sanchez John Alexander; Bueno Luciano de Souza Ribero (Journal of Electrical Bioimpedance)
The conductive polymeric electrodes using 3D printing are an innovative material development with the advantage of the flexibility of integrating isolated polymers with a higher electrical conductivity of carbon-based materials, generating new possibilities in environmental, healthcare, and food monitoring. Based on the morphology, geometric arrangement, and dielectric properties of the composites, the performance of the electrodes is improved. Structural designs are optimized to enhance functionalities such as adhesion, catalytic activity, and the reduction of interface energy. With these concepts, a functionalized carbon-based polymeric electrode was fabricated using 3D printing. The Differential Impedance Spectrum (DIS) was employed to analyze the response of functionalized electrodes to solutions of acetic acid and calcium chloride (CaCl2). DIS data extract the differential phase angle and indicate the interactions between the functionalized surface with acetic acid and CaCl2 solutions, showing noticeable peaks in three zones: at lower frequencies (< 10 kHz), medium frequencies range of 10 kHz to 100 kHz, and higher frequencies (> 100 kHz). In the three cases analyzed, the CaCl2 solution presented the highest frequency compared with acetic acid. When the sensor was doubled functionalized, the peaks were shifted between the range of 220 kHz to 280 kHz. A conclusion is that the carbon-based polymer electrode not only reduces manufacturing costs but also enables faster functionalization to detect specific chemical compounds in liquids quickly and portable without the need for higher-level equipment. These electrodes could be applied to make measurements in aqueous media such as ponds, pools, lakes, rivers, and oceans to detect contaminants, as well as in human fluids to recognize metabolites in sweat, urine, saliva, and blood.